Algoritma Media Digital dan Partisipasi Politik Warga Analisis Empiris dalam Konteks Demokrasi Indonesia - Ananta, Muhammad Fikri; Kartika Sari, Dewi (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of digital media algorithms has transformed the patterns of citizen political participation in Indonesian democracy. Social media platforms are no longer simply communication spaces but play an active role in filtering, sorting, and distributing political information. This study aims to empirically analyze the relationship between digital media algorithms and citizen political participation in the context of Indonesian democracy. The study uses a qualitative-empirical approach based on systematic literature analysis and thematic reviews of relevant previous research findings. The analysis focuses on algorithmic mechanisms, forms of digital political participation, and their implications for the quality of democracy. The analysis shows that algorithms contribute significantly to increasing the visibility of political issues and encouraging citizen engagement, particularly among the younger generation. However, algorithms also reinforce polarization, information enclaves, and practices of political discourse manipulation. These conditions directly impact the quality of public deliberation and the inclusiveness of political participation. This study confirms the ambivalent role of algorithms. Algorithms can expand political participation, but simultaneously have the potential to reduce democratic rationality and pluralism. These findings enrich the study of digital democracy in Indonesia and provide an empirical basis for formulating more accountable digital media governance policies.